Perceptions of drinking water quality from private wells in Alberta: A qualitative study. Issue 3 (3rd July 2019) - Munene, Abraham; Lockyer, Jocelyn; Checkley, Sylvia; Hall, David C.
Abstract: Water wells are important in providing water for rural populations that are far removed from municipal water supplies. Over 400, 000 rural Albertans use water wells for domestic purposes. The responsibility of well water management lies with well owners. Perceptions of well water quality become important in influencing the adoption of well water management practices such as testing, treatment, and well maintenance. This study sought to understand perceptions of well water quality among rural Albertans living on acreages and farms. Semi-structured interviews were conducted with well owners. A thematic analysis was used to analyze the data. Overall, well water owners were satisfied with the organoleptic properties of their well water. Activities perceived as a hazard to well water contamination were mainly agricultural or oil and gas related. Most well water owners reported using some form of mitigation strategy. Well water owners reported knowledge of well water contamination events and the main illnesses associated with well water contamination were gastrointestinal illnesses. Perceptions of well water quality were influenced by several factors. Identification of these factors is useful in the development of well stewardship policy and could help inform well stewardship programs in the province.